Policy, Risk and Spillover Analysis in the World Economy : A Panel Dynamic Stochastic General Equilibrium Approach - Vitek, Francis (IMF Working Papers; Working Paper ;, 2017)
This paper develops a structural macroeconometric model of the world economy, disaggregated into forty national economies, to facilitate multilaterally consistent macrofinancial policy, risk and spillover analysis. This panel dynamic stochastic general equilibrium model features a range of nominal and real rigidities, extensive macrofinancial linkages, and diverse spillover transmission channels. These macrofinancial linkages encompass bank and capital market based financial intermediation, with financial accelerator mechanisms linked to the values of the housing and physical capital stocks. A variety of monetary policy analysis, fiscal policy analysis, macroprudential policy analysis, spillover analysis, and forecasting applications of the estimated model are demonstrated. These include quantifying the monetary, fiscal and macroprudential transmission mechanisms, accounting for business cycle fluctuations, and generating relatively accurate forecasts of inflation and output growth.